Creative Communication is For You - Harold B. Swanson; Warren Gore (Journal of Applied Communications, 1976)
Would you sign a contract to add at least one new creative communications idea to your repertoire during the coming year? Why not? As communicators, we're constantly dealing with words, ideas, and thoughts, so why shouldn't we be leaders in creativity? Why shouldn't we teach by example?